Influence of laser treatment on tribologcal properties of microstructures of carbon ceramic coverages by an elektrosparks method - Radek, N.; Szalapko, J. (Problems of Tribology, 2014)
The effect of laser treatment on the properties of electro-applied coatings. Assessment of the properties of the coatings after laser treatment was based on observation of the microstructure, microhardness, roughness and tribological tests. The study was conducted using the electrode WC-Co-Al2O3, which were manufactured by sintering of nanostructured powders. Coatings applied using the device elec-8A EIL for samples of steel C45, and then melted Nd: YAG laser.